Sensorimotor specificities in balance control of expert fencers and pistol shooters - Herpin, G.; Gauchard, G. C.; Lion, A.; Collet, P.; Keller, D.; Perrin, P. P. (Journal of Electromyography and Kinesiology, 2010)
Motor skills during sport activity are influenced by practice-related constraints and leads to the development of appropriate postural sensorimotor strategies. Fencing is highly requiring visual monitoring and high-speed motor skills while retaining efficient balance control. Conversely, pistol shooting is a static activity requiring a high control of body sway. This study aimed to evaluate balance control and the related neurosensory organisation through reproducible postural tasks with and without sensory conflict. Twelve expert fencers, 10 expert shooters and 10 sedentary controls have performed a static posturographic test and a sensory organisation test (in 6 different sensory situations based upon sway-referenced vision and support surface, C1 to C6). Shooters yielded a better balance control during C1 (eyes open) and C2 (eyes closed) than fencers and controls. Fencers showed a better balance control in C5 (eyes closed with sway-referenced support surface) than shooters and controls. While this study confirms the beneficial effects of physical activities on balance control, a differential effect on balance characteristics due to the acquired specific motor skills was also noted. In addition to high proprioceptive sensitivity in sportsmen, dynamic constraints in fencing force fencers to permanently select the most relevant information to manage better sensory conflicting situations.